Incidence and Antiseizure Medications of Post-stroke Epilepsy in Umbria: A Population-Based Study Using Healthcare Administrative Databases - Costa, Cinzia; Nardi Cesarini, Elena; Eusebi, Paolo; Franchini, David; Casucci, Paola; De Giorgi, Marcello; Calvello, Carmen; Romoli, Michele; Parnetti, Lucilla; Calabresi, Paolo (Frontiers in Neurology, 2022)
Introduction Post-stroke epilepsy (PSE) requires long-term treatment with antiseizure medications (ASMs). However, epidemiology of PSE and long-term compliance with ASM in this population is still unclear. Here we report, through population-level healthcare administrative data, incidence, risk factors, ASM choice and ASM switch over long-term follow-up. Materials and methods This population-based retrospective study using Umbria healthcare administrative database. Population consisted of all patients with acute stroke, either ischaemic or haemorrhagic, between 2013 and 2018. ICD-9-CM codes were implemented to identify people with stroke, while PSE was adjudicated according to previously validated algorithm, including EEG and ≥1ASM seven days after stroke. Results Overall, among 11093 incident cases of acute stroke (75.9% ischemic), 275 subjects presented PSE, for a cumulative incidence of 2.5%. Patients with PSE were younger (64 vs 76 years), more frequently presented with haemorrhagic stroke, and had longer hospital stay (15.5 vs 11.2 days) compared to patients without PSE. Multivariable Cox proportional hazards models confirmed that PSE associated with haemorrhagic stroke, younger age and longer duration of hospital stay. Levetiracetam was the most commonly prescribed ASM (55.3%), followed by valproate and oxcarbazepine. Almost 30% of patients prescribed with these ASMs switched treatment during follow-up, mostly towards non-enzyme-inducing ASMs. Twelve percent of patients was prescribed ASM polytherapy over follow-up. Conclusions PSE is associated with haemorrhagic stroke, younger age, and longer hospital stay. First ASM is switched every one in three patients, suggesting the need for treatment tailoring in line with secondary prevention.